1993
DOI: 10.1182/blood.v82.7.2010.bloodjournal8272010
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of response to recombinant human erythropoietin in patients with the anemia of renal failure by serum transferrin receptor and fibrinogen

Abstract: Recombinant human erythropoietin (rHuEpo) has been shown to be effective in correcting the anemia of chronic renal failure, but the dose needed may be variable. The reason for this variation is not known, but several factors could be involved, such as iron deficiency, inflammation, aluminum intoxication, hyperparathyroidism, blood losses, or marrow dysfunction. Treatment with rHuEpo was given intravenously thrice weekly after hemodialysis to 64 consecutive unselected patients with the anemia of chronic renal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
6

Year Published

1994
1994
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 0 publications
0
17
0
6
Order By: Relevance
“…The semilogarithmic relationship between the serum Epo and the blood haemoglobin concentration in leishmaniasis patients was compared to the one in a reference group of persons not suffering from inflammation, as described recently ( El Hassan et al , 1997 ). The observed/predicted (O/P) ratio of log [Epo] was calculated for each serum sample according to Beguin et al (1993 ).…”
Section: Methodsmentioning
confidence: 99%
“…The semilogarithmic relationship between the serum Epo and the blood haemoglobin concentration in leishmaniasis patients was compared to the one in a reference group of persons not suffering from inflammation, as described recently ( El Hassan et al , 1997 ). The observed/predicted (O/P) ratio of log [Epo] was calculated for each serum sample according to Beguin et al (1993 ).…”
Section: Methodsmentioning
confidence: 99%
“…This was also corroborated in the present study by the fact that platelet increments over baseline correlated with the degree of expansion of erythropoietic activity as measured by sTfR and Hct changes. In a previous paper, we have shown that patients with functional iron deficiency did not increase sTfR levels in response to rHuEpo (42). Also, platelet counts did not change in non-responders until the Epo dose was increased and erythropoiesis had begun to expand.…”
Section: Discussionmentioning
confidence: 81%
“…It was also observed in MDS patients that responders to EPO therapy had significantly higher pretreatment Hb concentrations (19). Serum TfR, which is known to reflect the level of bone marrow net erythropoiesis and to serve as useful index for red cell production (20), is reported to be a predictive parameter for responses to EPO therapy in the anemia of chronic renal failure (21) and the chronic anemia of cancer (22). Taken together, these 5 parameters that differentiate responders from non-responders suggest that responding patients had less advanced anemia, probably due to the preserved erythropoietic ability of bone marrow.…”
Section: Discussionmentioning
confidence: 99%